2013
DOI: 10.5089/9781484328446.001
|View full text |Cite
|
Sign up to set email alerts
|

Global Spillovers into Domestic Bond Markets in Emerging Market Economies

Abstract: While fiscal conditions remain healthier than in advanced economies, emerging economies continue to be exposed to negative spillovers if global conditions were to become less favorable. This paper finds that domestic bond yields in emerging economies are heavily influenced by two international factors: global risk appetite and global liquidity. Using a novel approach, the analysis goes on to show that the vulnerability of emerging economies to these factors is not uniform but rather depends on country specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
2
11
1
Order By: Relevance
“…Chen (2014) highlights the dominant role played by VIX in linking the expected market volatilities of the United States, Canada, Germany, and Japan. Jaramillo and Weber (2013) show that bond yields in EMs are heavily influenced by global risk appetite as proxied by VIX. The author shows that an increase in VIX lowers stock market returns, bond yields, and currency values in Australia and New Zealand.…”
Section: Literature Review: Vix As Risk Indicatormentioning
confidence: 99%
See 1 more Smart Citation
“…Chen (2014) highlights the dominant role played by VIX in linking the expected market volatilities of the United States, Canada, Germany, and Japan. Jaramillo and Weber (2013) show that bond yields in EMs are heavily influenced by global risk appetite as proxied by VIX. The author shows that an increase in VIX lowers stock market returns, bond yields, and currency values in Australia and New Zealand.…”
Section: Literature Review: Vix As Risk Indicatormentioning
confidence: 99%
“…Nikkinen and Sahlström (2004) find that changes in VIX are the leading source of uncertainty in U.K., German, and Finish equity markets. Jaramillo and Weber (2013) show that bond yields in EMs are heavily influenced by global risk appetite as proxied by VIX. However, none of these international market studies examine the predictive power of VIX for equity returns in the worldwide regional EMs as well as in overall EMs and FMs.…”
Section: Literature Review: Vix As Risk Indicatormentioning
confidence: 99%
“…() found strong evidence of spillover effects in the sovereign bond market from advanced to emerging economies. Jaramillo and Weber (,b) estimated that domestic bond yields in emerging economies are significantly influenced by global risk appetite and liquidity conditions. On the contrary, Peiris () showed that greater foreign participation in the government bond market tends to reduce volatility in bond yields in emerging markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Covering the period 1999–2007, Büttner and Hayo () found that market capitalisation, interest rate spreads and business cycle synchronisation are the major determinants of stock market integration among EU countries. Jaramillo and Weber (,b) showed that fiscal fundamentals, financial sector openness and the external current account balance play a leading role in explaining the global spillovers in the emerging bond markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our paper extends their work by more thoroughly estimating the dynamics of the world interest rate, relying on a large and updated sample of countries, and, most importantly, using the estimates to gauge the extent to which emerging markets are integrated into world capital markets. Jaramillo and Weber (2013) rely on a common factor approach, as we do, to examine yields in emerging markets, but do not estimate a FAVAR; they focus primarily on estimating common factors across emerging markets and do not link interest rates in developed economies to developing economies.…”
Section: Introductionmentioning
confidence: 99%